2023
DOI: 10.3389/fpls.2023.1060747
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of volatiles in flowers from four Rosa chinensis cultivars by HS-SPME-GC × GC-QTOFMS

Abstract: Rosa chinensis cultivars with volatile aromas are important resources in the perfume industry. The four rose cultivars introduced to Guizhou province are rich in volatile substances. In this study, volatiles from four Rosa chinensis cultivars were extracted using headspace-solid phase microextraction (HS-SPME), and analyzed with two-dimensional gas chromatography quadrupole time of flight mass spectrometry (GC × GC-QTOFMS). A total of 122 volatiles were identified; the main compounds in these samples were benz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…These compounds are also highly reported representative compounds of Ferula . Studies have shown that terpene compounds mostly have floral, citrus, and woody aroma ( Quan et al., 2023 ), which contributes to the aroma of Ferula . Alcohols and aldehydes are mostly fresh and grassy compounds, while compounds unique to F. feurlaeoides mostly have floral and fruity aroma.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds are also highly reported representative compounds of Ferula . Studies have shown that terpene compounds mostly have floral, citrus, and woody aroma ( Quan et al., 2023 ), which contributes to the aroma of Ferula . Alcohols and aldehydes are mostly fresh and grassy compounds, while compounds unique to F. feurlaeoides mostly have floral and fruity aroma.…”
Section: Discussionmentioning
confidence: 99%
“…And among most varieties, geraniol has the highest OAV in “H50” and has a fruity fragrance [ 28 ]. Benzenemethanol has the highest OAV in “H2”, “H14”, and “H55” and has a rose flavor [ 29 ]. 3-furanmethanol also has a sweet aroma and has the highest OAV in “H38” and “H52” [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since this flower blooms year-round and produces flowers with diverse colors [28], it has been widely planted and cultivated as an ornamental plant. This flower also has many other values, e.g., cultural [29], medicinal [30,31], and edible [32,33]. These values are attributed to the abundance of an-thocyanin in the petals, but the anthocyanin content significantly affects these values.…”
Section: Accurate Detection and Quantitative Assessment Of Anthocyani...mentioning
confidence: 99%